PENGARUH SARANA DAN PRASARANA PERPUSTAKAAN TERHADAP MINAT KUNJUNGAN SISWA DI SMA NEGERI 11 BONE - Kasmawati; Astina (Educational Leadership: Jurnal Manajemen Pendidikan, 2022)
This study aims to find out how the library facilities and infrastructure at SMA Negeri 11 Bone, then to find out how the interest of students visiting the library at SMA Negeri 11 Bone, and to determine whether or not there is an influence between library facilities and infrastructure on student interest in SMA Negeri 11 Bone. This research is a quantitative research. The sample is 249 students using the Simple Random Sampling technique. Data collection techniques using questionnaires and documentation. Data processing techniques using descriptive analysis techniques and inferential analysis. The results showed that library facilities and infrastructure were in the medium category with a percentage of 71%. Interest in student visits to the library is also in the moderate category with a percentage of 74%. There is a significant influence between library facilities and infrastructure on student interest in visiting SMA Negeri 11 Bone.